Acknowledgment of Reviewers’ Contribution - Praxis, Journal of Transformative (Journal of Transformative Praxis, 2021)
The Journal of Transformative Praxis is a collaborative venture between Tribhuvan University (TU), Kathmandu University (KU), and the Norwegian University of Life Sciences (NMBU). The Editorial Board of the Journal would like to appreciate their contributions to the following reviewers for their scholarly efforts in reviewing manuscripts submitted to the JrTP.